The Innovation of Talent Training Mode in Intelligent Control Technology with the Empowerment of Artificial Intelligence from the Perspective of New Quality Productivity - Liu, Shiqi (Journal of Theory and Practice of Management Science, 2025)
Under the promotion of new quality productivity, social and economic development has entered a new stage, and technological innovation has gradually become a key driving force for economic growth. Mechanical and electrical control is an important component of intelligent control technology, and the training mode of its professional talents directly affects the development speed of social informatization. The rapid development of artificial intelligence technology provides unprecedented opportunities for educational innovation in the field of mechanical and electrical control. In view of this, this study focuses on exploring the talent cultivation mode of artificial intelligence empowering innovative electromechanical control majors from the perspective of new quality productivity, and proposes effective specific implementation strategies to cultivate high-quality and high skilled talents that can regulate the future development needs of the industry, providing certain reference and guidance.